2018
DOI: 10.1002/ijc.31846
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and health effects in the upper respiratory tract associated with tobacco smoking other than cigarettes

Abstract: The objective of the review was to compare molecular and health effects of tobacco smoking using cigars, cigarillos, pipe and water pipe in relation to the effects of cigarette smoking. In this review we will focus on the upper respiratory tract. Mechanisms of interaction of tobacco smoke constituents after products other than cigarettes are similar to these associated with cigarette smoking. Carcinogenic activity was demonstrated for any type of tobacco smoking, although the risk of developing head and neck s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 105 publications
(237 reference statements)
0
15
0
Order By: Relevance
“…In agreement with the health risks identified to date, analytical examination of the components in WP smoke include a mixture of chemicals with known or suspected disease-causative agents that closely resemble those found in cigarette smoke (CS), and in many cases at higher concentrations 20 21. Indeed, WP is estimated to deliver to cells and tissues a similar group of toxicants that are known to dysregulate cell molecular mechanisms, including DNA repair and methylation 22–26. Herein, we investigated the effects of lung health using a murine model by analysing inflammation and pulmonary function after chronic WP exposure for 6 months.…”
Section: Introductionmentioning
confidence: 95%
“…In agreement with the health risks identified to date, analytical examination of the components in WP smoke include a mixture of chemicals with known or suspected disease-causative agents that closely resemble those found in cigarette smoke (CS), and in many cases at higher concentrations 20 21. Indeed, WP is estimated to deliver to cells and tissues a similar group of toxicants that are known to dysregulate cell molecular mechanisms, including DNA repair and methylation 22–26. Herein, we investigated the effects of lung health using a murine model by analysing inflammation and pulmonary function after chronic WP exposure for 6 months.…”
Section: Introductionmentioning
confidence: 95%
“…One in vitro study concluded that water-soluble polymer-encapsulated nano-luteolin from hydrophobic luteolin (PLA-PEG) inhibited the growth of lung cancer cells (H292 cell line) and squamous cell carcinoma of head and neck (SCCHN) cells (Tu212 cell line) [ 86 ], which are among the most frequent cancers worldwide [ 87 , 88 , 89 ]. Moreover, in vivo study using a tumour xenograft mouse model demonstrated that nano-luteolin has a significant inhibitory effect on the tumour growth of SCCHN in comparison to free luteolin [ 86 ].…”
Section: Luteolinmentioning
confidence: 99%
“…The high prevalence of tobacco consumption and its detrimental effects on human health make it difficult to curb the associated mortality. Tobacco use increases the risk of cardiovascular disease [ 8 , 9 ], respiratory disease [ 10 , 11 , 12 ], and cancer [ 13 , 14 , 15 , 16 ]. Indeed, tobacco is the largest preventable cause of cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%